2019
DOI: 10.1016/j.disc.2019.01.019
|View full text |Cite
|
Sign up to set email alerts
|

On a family of highly regular graphs by Brouwer, Ivanov, and Klin

Abstract: Highly regular graphs for which not all regularities are explainable by symmetries are fascinating creatures. Some of them like, e.g., the line graph of W. Kantor's non-classical GQ(5 2 , 5), are stumbling stones for existing implementations of graph isomorphism tests. They appear to be extremely rare and even once constructed it is difficult to prove their high regularity. Yet some of them, like the McLaughlin graph on 275 vertices and Ivanov's graph on 256 vertices are of profound beauty. This alone makes it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Recently, in [48] a classical family of strongly regular graphs originally constructed by Brouwer, Ivanov, and Klin (see [7]) was analyzed for regularities. It was shown there that these graphs are (3, 5)-regular but not 2-homogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in [48] a classical family of strongly regular graphs originally constructed by Brouwer, Ivanov, and Klin (see [7]) was analyzed for regularities. It was shown there that these graphs are (3, 5)-regular but not 2-homogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is proved in Appendix A. In [29] it is announced that Σ (m) is even (3, 5)-regular, but we are not aware of a proof in print.…”
Section: Binary Vector Spaces With a Quadratic Formmentioning
confidence: 92%
“…In [29] it is shown that the graphs Γ (m) are triplewise 5-regular, a.k.a. (3,5)-regular, where (s, t)-regularity is the analog of the t-vertex condition where s instead of two vertices are distinguished.…”
Section: Binary Vector Spaces With a Quadratic Formmentioning
confidence: 99%